2013
DOI: 10.1186/1687-9856-2013-15
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of gender assignment in 17β-hydroxysteroid dehydrogenase type 3 deficiency: is there a role for early orchiectomy?

Abstract: Background17β-Hydroxysteroid dehydrogenase type-3 (17βHSD-3) deficiency is a rare cause of 46,XY disorders of sex development. The enzyme converts androstenedione to testosterone, necessary for masculinization of male genitalia in utero. 17βHSD-3 deficiency is frequently diagnosed late, at puberty, following virilization, with consequent female-to-male gender reassignment in 39-64%. The decision for sex of rearing is difficult, especially if diagnosed in early childhood. Consensus guidelines are equivocal or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
3
22
0
2
Order By: Relevance
“…Recent studies confirmed previous reports of a high rate of later patient-initiated gender change [55,56], although the risk may be smaller if gonadectomy has been performed prior to puberty. Interestingly, in one study no actual gender change was reported in the diagnostic groups [64], but gender identities of participants were not all typically female.…”
Section: Changes In Gender Assignment Policies For Newborns With Genisupporting
confidence: 75%
See 1 more Smart Citation
“…Recent studies confirmed previous reports of a high rate of later patient-initiated gender change [55,56], although the risk may be smaller if gonadectomy has been performed prior to puberty. Interestingly, in one study no actual gender change was reported in the diagnostic groups [64], but gender identities of participants were not all typically female.…”
Section: Changes In Gender Assignment Policies For Newborns With Genisupporting
confidence: 75%
“…Moreover, postnatal androgens may contribute to long-term gender outcome, both in early infancy [54] and at later stages, then perhaps mediated not only through organizational effects of sex hormones on the developing brain, but also through virilization of the body and associated effects on self-image and on the reactions of the social environment, as seen in cases of 46,XX CAH with poor hormonal control [47] and in untreated 5α-reductase-2 deficiency [55] and 17β-hydroxysteroid dehydrogenase-3 deficiency [56]. Such issues need to be considered in gender assignment decisions.…”
Section: Gender Development In Individuals With Dsdmentioning
confidence: 99%
“…Because DEPTOR was an mTOR inhibitor [23], the activity of mTORC1 was examined at first. When the mTOR signaling pathway was activated, the phosphorylation of PS6 (S235/236) was upregulated [23].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been suggested that unidentified pre-and postnatal factors, a better knowledge of the natural history of the disorder in some areas, and sociocultural issues may participate, all together, in influencing gender identity and role [77,161,163]. In fact, biological factors aside, socialization and learning, have been shown to contribute significantly to gender identity and role [168]. Up to now, data supporting a male gender assignment in these subjects are not as strong as for 5-alpha-reductase deficiency.…”
Section: -Beta-hsd-3 Deficiencymentioning
confidence: 99%
“…Moreover, it should be taken into account that an intermediate risk for germ-cell tumors exists for 17-beta-HSD-3 deficiency, and there are no reports of fertility thus far [140]. In particular, regarding the latter, it is unknown whether early testosterone therapy and orchidopexy would result in a more favorable outcome [168]. Consequently, female gender assignment may be appropriate in some situations; regular testicular evaluation is required for those reared male who have not had their testes removed [147].…”
Section: -Beta-hsd-3 Deficiencymentioning
confidence: 99%